Pengaruh permusuhan konsumen terhadap niat boikot pada merek McDonald’s melalui kontrol perilaku yang dirasakan - Kholisoh, Titik Dewi; Widyastuti (Universitas Negeri Surabaya, 2025)
This study investigates the effect of consumer animosity on boycott intention toward the McDonald’s brand, with perceived behavioral control as a mediating variable. Referencing McDonald’s official website, in 2023 the company set a global system sales growth target of 4–5% annually by 2027. However, in the second quarter, global sales declined by 1%, missing the expected 0.5% increase. Additionally, negative sentiment toward McDonald’s surged to 528 mentions, compared to 229 positive.The research used a sample of 220 respondents who had never previously boycotted McDonald’s, were aware of its political affiliations, and had been exposed to the BDS (Boikot, Divestment, Sanctions) Movement. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was employed using SmartPLS 3.29 software.Results show that consumer animosity has a significant positive effect on perceived behavioral control, which in turn positively influences boycott intention. Consumer animosity also directly influences the intention to boycott, with perceived behavioral control serving as a significant mediating factor.The managerial implication suggests that McDonald’s should adopt a proactive strategy to manage reputational risk stemming from political controversies. This includes enhanced employee training, meaningful consumer engagement, and the use of data-driven decision-making to safeguard brand trust and sustain long-term performance.